KETERAMPILAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN SCRABBLE PADA SISWA SMP DI KABUPATEN BOGOR - Sigit Widiyarto; Aster Pujaning Ati; Mulyadi; Sepni Yanti; Restoeningroem; Toto Widiarto, Sutina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the use of Scrabble as a learning media to improve Junior High School students’ writing skills in explanation texts. The study addresses the low interest and writing ability of students and emphasizes the need for effective and appropriate learning media. The research employed a Classroom Action Research (CAR) method with 94 students from three Junior High Schools in Bogor as respondents. The results showed an improvement in students’ writing skills across cycles 2 and 3, with a total improvement of 8 points. Students also became more confident and faster in constructing sentences within explanation texts. The teaching and learning process involved opening, core, and closing activities. Through Scrabble media, students could transform words into coherent paragraphs. It is recommended that teachers develop other similar or innovative learning media, ensuring adequate preparation of materials, time, and guided instruction.